Notoginsenoside R1 Protects Against Diabetic Cardiomyopathy Through Activating Estrogen Receptor α and Its Downstream Signaling - Zhang, Bin; Zhang, Jingyi; Zhang, Chenyang; Zhang, Xuelian; Ye, Jingxue; Kuang, Shihuan; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2018)
Diabetic cardiomyopathy (DCM) leads to heart failure and death in diabetic parents, no effective treatment is available. Notoginsenoside R1 (NGR1) is a novel saponin that is derived from Panax notoginseng and our previous studies have showed cardioprotective and neuroprotective effects of NGR1. However, its role in protecting against DCM remains unexplored. Herein, we examine potential effects of NGR1 on cardiac function of diabetic db/db mice and H9c2 cardiomyocytes treated by advanced glycation end products (AGEs). In vitro experiments revealed that pretreatment with NGR1 significantly decreased AGEs-induced mitochondria injury, limited an increase in ROS, and reduced apoptosis in H9c2 cells. NGR1 eliminated ROS by promoting estrogen receptor α expression, which subsequently activated Akt and Nrf2-mediated anti-oxidant enzymes. In vivo investigation demonstrated that NGR1 significantly reduced serum lipid levels, insulin resistance, the expression of enzymes related to cardiomyopathy, and the expression of apoptotic proteins. Finally, NGR1 improved cardiac dysfunction and attenuated histological abnormalities, as evidenced by elevating ejection fraction and fractional shortening, and reducing cardiac fibrosis. Mechanistically, NGR1 selectively promoted ERα expression, which led to the activation of Akt-Nrf2 signaling and the inhibition of the TGFβ pathway. Collectively, these results strongly indicate that NGR1 exerts cardioprotective effects against diabetic cardiomyopathy through its inhibition of oxidative stress and apoptosis, and eventually suppresses cardiac fibrosis and hypertrophy, which suggests that NGR1 is a potential therapeutic medicine for the treatment of DCM.